Distributed Landscape Design System. Issue 1 (February 2020) - Yao, Jinxiu; Xie, Mingda
Abstract: The landscape design as the human living space geographical composition is very important part of ecological system, the existence of regional landscape not only provides residents with a versatility, layout, balanced, open outdoor public space of free activities, whereas in the past the landscape design of the system is designed in accordance with the local geographical factors, more is not fully consider various comprehensive factors. The purpose of this paper is to properly introduce the existing technology based on distributed theory such as remote sensing positioning and data analysis to optimize the landscape design system. By using the data sensing module of Hadoop landscape design system and the distributed coding technology for genetic algorithm, the application of 3D landscape design is carried out. Its characteristic and innovation is the fusion of distributed storage and cluster, the design of big data dynamic storage system, analysis of its operation depends on the analysis and algorithm technology, compared with the final system operation effect. Experimental results show that the landscape design system based on distributed very well to the geographical location, topography, the surrounding environment, traffic conditions, historical and cultural factors, such as analysis, determine the theme of the landscape planning and design positioning, functional partition and content of ecological landscape, through the analysis of the landscape planning and design, take its long, avoid its short, problem solving, superposition of advantages, for a more reasonable and high quality to complete the landscape planning and design is of great significance.